Determinants of Delay in Seeking Malaria Treatment for Under-Five Children at Gambella Town, Southwest Ethiopia: A Case-Control Study - Addisu Tona Shumerga; Habtamu Jarso Hebo; Tsegaye Tewelde Gebrehiwot; Mamo Nigatu Gebre (Journal of Tropical Medicine)
Background. Most of the malaria-related complications in children are due to delay in the treatment-seeking of caregivers. The objective of this study was to identify determinants of delay in seeking malaria treatment for under-five children in Gambella town, Ethiopia. Methods. A case-control study was conducted in March 2017 among caregivers/parents consecutively included in the study. Data were collected by face-to-face interviews using a structured questionnaire. Descriptive statistics and logistic regression were, respectively, used for descriptive and analytical data analyses. Adjusted odds ratios and 95% CI were, respectively, calculated to assess the strength of association and statistical significance. Result. A total of 153 cases and 153 control caregivers/parents participated in the study giving a response rate of 100%. The mean age of cases and controls was 29.4 years (SD ± 6.0 years) and 29.63 years (SD ± 7.8 years), respectively. Being housewife (AOR = 2.50; 95% CI: 1.47–4.22), having no history of child mortality (AOR = 3.70; 95% CI: 1.79–7.64), and chewing khat (AOR = 3.50; 95% CI: 1.57–7.68) were significantly associated with delay in seeking malaria treatment for under-five children among the caregivers. Conclusion and Recommendation. Comprehensive community-based malaria prevention and control education should be given for the caregivers in the town giving due emphasis to housewives, khat-chewers, and the caregivers with no story of child death to better promote early malaria treatment-seeking for under-five children.